2014
DOI: 10.3390/polym6102684
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered Proteins: Where Computation Meets Experiment

Abstract: Proteins are heteropolymers that play important roles in virtually every biological reaction. While many proteins have well-defined three-dimensional structures that are inextricably coupled to their function, intrinsically disordered proteins (IDPs) do not have a well-defined structure, and it is this lack of structure that facilitates their function. As many IDPs are involved in essential cellular processes, various diseases have been linked to their malfunction, thereby making them important drug targets. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 190 publications
(251 reference statements)
2
56
0
Order By: Relevance
“…It was also emphasized that functional conformational changes and the allosteric behavior of globular proteins can rely on the existence of conformational substates, which can be described as the atomic displacements leading to the formation and interconversion of different local configurations of the same overall protein structure [69,70,71,72,73,74,75]. This idea is illustrated by Figure 2, which represents the potential energy landscapes of ordered and disordered proteins [76]. The energy landscape of ordered proteins is characterized by a specific funnel-like shape, where a broad mouth at the top represents a set of unfolded conformations and the narrow end at the bottom shows the lowest energy state that corresponds to the native structure [77,78,79,80,81].…”
Section: Proteoformsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also emphasized that functional conformational changes and the allosteric behavior of globular proteins can rely on the existence of conformational substates, which can be described as the atomic displacements leading to the formation and interconversion of different local configurations of the same overall protein structure [69,70,71,72,73,74,75]. This idea is illustrated by Figure 2, which represents the potential energy landscapes of ordered and disordered proteins [76]. The energy landscape of ordered proteins is characterized by a specific funnel-like shape, where a broad mouth at the top represents a set of unfolded conformations and the narrow end at the bottom shows the lowest energy state that corresponds to the native structure [77,78,79,80,81].…”
Section: Proteoformsmentioning
confidence: 99%
“…The energy landscape of ordered proteins is characterized by a specific funnel-like shape, where a broad mouth at the top represents a set of unfolded conformations and the narrow end at the bottom shows the lowest energy state that corresponds to the native structure [77,78,79,80,81]. On the contrary, IDPs are characterized by a relative flat but rough energy landscape with multiple local energy minima separated by small barriers [14,33,76,82]. Finally, careful analysis of the bottom of the funnel-shaped energy landscape revealed that, for many proteins, the surface of the energy minimum is actually not smooth, being rough because of the presence of many smaller minima corresponding to different states sampled by the protein (see Figure 2).…”
Section: Proteoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, crystallizing a disordered protein is not possible precisely because the process of crystallization requires the protein in question to adopt similar structures within the crystal environment (20 -22). Structural modeling has therefore played an essential role in the study of very disordered systems (20,23,24). Dynamical simulations, for example, combined with restraints derived from NMR and/or SAXS experiments can be used to model important structural features of these proteins (21,25,26).…”
Section: An Order-structure Continuum For Describing Protein Structurementioning
confidence: 99%
“…1 schematically representing the potential energy landscape of an ordered protein. 45 Although such landscape is traditionally considered as a folding funnel with a large set of unfolded conformations constituting a broad mouth at the top of the funnel, and with the lowest energy state corresponding to the native structure being located at the narrow end at the bottom of funnel, [46][47][48][49][50] careful analysis revealed that the surface of the bottom of the funnel for many globular proteins is actually not smooth, being rough or rugged, reflecting the presence of many smaller minima corresponding to different substates sampled by the a protein (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%